Exploring the Changes in Mild Cognitive Impairment Blood-Based Biomarkers after Local Antibiotic Periodontal Treatment in Diabetic Patients: Secondary Analysis of Data from a Randomized Controlled Trial - Ramadhani, Aulia; Tanaka, Azusa; Minagawa, Kumiko; Takehara, Sachiko; Yamada, Takaho; Sone, Hirohito; Kaneko, Noboru; Nohno, Kaname; Ogawa, Hiroshi (European Journal of Dentistry, 2024)
Objectives This article investigates the changes in blood-based biomarkers associated with mild cognitive impairment (MCI) risk in type 2 diabetic patients following local antibiotic periodontal treatment.Materials and Methods A secondary analysis of data from a 24-week randomized controlled trial was conducted, involving 27 patients with type 2 diabetes mellitus and periodontitis. Participants received periodontal treatment biweekly from baseline until the 6th week of the study. Fourteen patients in intervention group received scaling with local antibiotic adjunct (Periofol 2%). The outcomes were periodontal inflammation score, which was measured using periodontal inflamed surface area, the inflammation markers levels (tumor necrosis factor-α, C-reactive protein, and interleukin [IL]-6), and MCI risk score, which was assessed using protein plasma analysis through blood test. The evaluations were performed at baseline and week 24th in both groups. The changes in periodontal inflammation scores, inflammation parameters, and MCI risk in baseline and week 24th were analyzed.Statistical Analysis The Wilcoxon signed-rank test was used for within-group analysis and the Mann–Whitney U test was utilized for between-group analysis.Results Periodontal parameters were improved in both groups (p < 0.05). IL-6, complement C3, and alpha-2-antiplasmin levels were significantly decreased in the intervention group (p < 0.05). In between-group comparisons, there was a significant difference between the control and intervention groups in apolipoprotein A1, apolipoprotein C1, and alpha-1-B glycoprotein levels in week 24th (p < 0.05).Conclusion Even though the periodontal status showed significant improvement after being given local antibiotic periodontal treatment, the changes in MCI risk proteins plasma remained unclear.
Keywords: periodontitis; diabetes; mild cognitive impairment; periodontal treatment; inflammation